Media Pembelajaran Pengenalan Alat Transportasi dan Rambu Lalu Lintas Berbasis Android untuk Sekolah Dasar - Nadiyasari Agitha; Romi Saefudin; I Gede Pasek Suta Wijaya (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
Transportation equipment and traffic signs are one of the important lessons for elementary school students. However, many elementary school students only know the means of transportation without knowing the traffic signs. The purpose of this study is to build and create learning media to make it easier for students to recognize transportation tools and traffic signs using the Android platform. The method used in building this application is the waterfall method, which starts with making observations to testing the system. The tests used are black box testing and Mean Opinion Score (MOS). The results of the black box testing test are that the menu has been able to run according to their respective functions, while for MOS, it produces about 98% results stating that the application is running well. So that this application is used in accordance with the needs of elementary school students in helping to recognize means of transportation and traffic signs.